2005
DOI: 10.1186/1742-4690-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: HIV-1 Tat activates transcription of HIV-1 viral genes by inducing phosphorylation of the C-terminal domain (CTD) of RNA polymerase II (RNAPII). Tat can also disturb cellular metabolism by inhibiting proliferation of antigen-specific T lymphocytes and by inducing cellular apoptosis. Tat-induced apoptosis of T-cells is attributed, in part, to the distortion of microtubules polymerization. LIS1 is a microtubule-associated protein that facilitates microtubule polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 43 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…This is demonstrated by the present findings with regard to Tat(1-86) effects on tubulin polymerization, as well as other preparations employing purified tubulin [16, 17] and evidence that Tat(1-72) co-immunoprecipitates with LIS-1 [20]. It has also been shown that exposure to Tat variants affect the integrity of cytoskeletal proteins by initiation of oxidative stress mechanisms.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is demonstrated by the present findings with regard to Tat(1-86) effects on tubulin polymerization, as well as other preparations employing purified tubulin [16, 17] and evidence that Tat(1-72) co-immunoprecipitates with LIS-1 [20]. It has also been shown that exposure to Tat variants affect the integrity of cytoskeletal proteins by initiation of oxidative stress mechanisms.…”
Section: Discussionsupporting
confidence: 78%
“…For instance, it has been reported that exposure to 100 μM recombinant Tat(1-72) delays polymerization of porcine brain tubulin, and the authors suggest this occurs by competition for MAP-binding sites [10]. The interpretation of the findings by Battaglia et al [10] are supported by findings that Tat(1-72) co-immunoprecipitated with the MAP LIS1 in Tat-transfected HeLa cells [20]. Conversely, exposure of lamb brain-derived tubulin has shown facilitation of MAP-independent tubulin polymerization with exposure to the variant Tat (38-72) [17].…”
Section: Discussionmentioning
confidence: 93%
“…The HIV-1 Tat protein, which activates transcription of HIV-1 viral genes, has been shown to induce apoptosis of T cells, in part, by virtue of distorting microtubule polymerization through its interactions with Lis1 (38, 39). Poliovirus protein 3A has been shown to exhibit anti-apoptotic activity, owing to its ability to bind and inactivate Lis1, thereby blocking membrane protein trafficking and deregulating cell division (40).…”
Section: Discussionmentioning
confidence: 99%
“…These results increase the differences between the behaviour of extra and intracellular Tat. Other possible explanation is that Tat localizes predominantly in the nucleus when is synthesized inside the cell, but it remains mainly at the cytosol after being endocytosed ( 17 ), where it could be retained through the binding to cytoskeletal proteins as actin, tubulin, Lis1 and Hic ( 19 , 110 , 111 ), causing higher toxicity.…”
Section: Discussionmentioning
confidence: 99%